BENEFITS OF ONLINE EDUCATION TO THE INDUSTRY OF UZBEKISTAN (Лучшие интеллектуальные исследования, 2025)
Abstract: This article helps to show the productivity impact of online education in the industry of Uzbekistan. Along with the development of modern technologies, online education plays an important role in improving the skills of employees and providing them with new knowledge. Courses in modern technologies, management, quality control and other important directions are offered to the industry through online educational platforms of Uzbekistan.